Non-Markovianity through Accessible Information - Fanchini, F. F. [UNESP]; Karpat, G. [UNESP]; Cakmak, B.; Castelano, L. K.; Aguilar, G. H.; Jimenez Farias, O.; Walborn, S. P.; Souto Ribeiro, P. H.; Oliveira, M. C. de (Amer Physical Soc, 2014)
The degree of non-Markovianity of quantum processes has been characterized in several different ways in the recent literature. However, the relationship between the non-Markovian behavior and the flow of information between the system and the environment through an entropic measure has not been yet established. We propose an entanglement-based measure of non-Markovianity by employing the concept of assisted knowledge, where the environment E, acquires information about a system S, by means of its measurement apparatus A. The assisted knowledge, based on the accessible information in terms of von Neumann entropy, monotonically increases in time for all Markovian quantum processes. We demonstrate that the signatures of non-Markovianity can be captured by the nonmonotonic behavior of the assisted knowledge. We explore this scenario for a two-level system undergoing a relaxation process, through an experimental implementation using an optical approach that allows full access to the state of the environment.